2016
DOI: 10.1371/journal.pone.0154229
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterisation of Small Molecule Agonists Effect on the Human Glucagon Like Peptide-1 Receptor Internalisation

Abstract: The glucagon-like peptide receptor (GLP-1R), which is a G-protein coupled receptor (GPCR), signals through both Gαs and Gαq coupled pathways and ERK phosphorylation to stimulate insulin secretion. The aim of this study was to determine molecular details of the effect of small molecule agonists, compounds 2 and B, on GLP-1R mediated cAMP production, intracellular Ca2+ accumulation, ERK phosphorylation and its internalisation. In human GLP-1R (hGLP-1R) expressing cells, compounds 2 and B induced cAMP production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 49 publications
(104 reference statements)
0
37
0
Order By: Relevance
“…The structural relevance of various domains of GLP-1R has been elucidated by numerous studies (Thompson and Kanamarlapudi 2013, 2015a. The pathway(s) required for agonist-induced GLP-1R internalization has also been elucidated (Thompson and Kanamarlapudi 2015b). GLP-1 analogues are currently used to treat type 2 diabetes to promote normoglycemia in patients (Thompson and Kanamarlapudi 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The structural relevance of various domains of GLP-1R has been elucidated by numerous studies (Thompson and Kanamarlapudi 2013, 2015a. The pathway(s) required for agonist-induced GLP-1R internalization has also been elucidated (Thompson and Kanamarlapudi 2015b). GLP-1 analogues are currently used to treat type 2 diabetes to promote normoglycemia in patients (Thompson and Kanamarlapudi 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Endocytosis in this manner can lead to fission of caveolae enriched vesicles and then fusion with caveosomes (Thompson and Kanamarlapudi 2013). The Gaq pathway has recently been shown to be important for the agonist-induced GLP-1R internalization (Thompson and Kanamarlapudi 2015b). GLP-1R resensitization is not well studied but it has been shown that GLP-1R-mediated calcium signalling resensitizes within 1 h after agonist removal (Graaf et al 2016).…”
Section: The Ecls Of Gpcrs Have Been Demonstratedmentioning
confidence: 99%
See 3 more Smart Citations